Short-term adverse events after COVAXIN vaccination in adolescents (15–18 Years) in Northern India: Frequency, predictors, and reporting behavior - Sujoy Bose; Arpita Bhriguvanshi; Mehul Saxena (Clinical Epidemiology and Global Health, 2025)
Background: India initiated COVID-19 vaccination for adolescents (aged 15–18 years) on January 3, 2022, exclusively using COVAXIN. Adolescent-specific safety data remain limited, and adverse event following immunization (AEFI) reporting is notably low. This study evaluated the frequency, characteristics, and predictors of adolescents' short-term, self-reported AEFI post-COVAXIN vaccination and assessed their awareness and practices regarding official AEFI reporting mechanisms. Methods: A retrospective cohort study was conducted between May and September 2022 among 411 adolescents vaccinated with at least one dose of COVAXIN across schools in urban and rural Lucknow, Northern India. Data on demographics, vaccine doses, AEFI symptoms, onset, duration, management, prior SARS-CoV-2 infection, and awareness and reporting behaviors were collected via a validated questionnaire through face-to-face interviews. Results: 65.45 % reported AEFI after the first dose and 56 % after the second. The most common reactions included injection-site pain, fever, and headache, predominantly occurring within 12 h and resolving within three days. Females reported significantly higher AEFI frequency (Adjusted OR = 3.0; 95 %CI:1.23–7.37), and the first dose was associated with greater reactogenicity (Adjusted OR = 1.55; 95 %CI:1.14–2.09). Prior SARS-CoV-2 infections significantly influenced AEFI occurrence. Despite frequent mild, self-limiting symptoms, awareness of official AEFI reporting mechanisms was low (18 %), with only 1.2 % formally reporting their symptoms. Conclusion: COVAXIN vaccination in adolescents demonstrated a favorable short-term safety profile with predominantly mild, transient reactions. However, critically low awareness and negligible formal reporting highlight an urgent need to strengthen vaccine safety monitoring and public education on reporting practices.